Constructing aptamer anchored nanovesicles for enhanced tumor penetration and cellular uptake of water soluble chemotherapeutics. (15th April 2016) - Li, Xin; Zhu, Xiumei; Qiu, Liyan
Graphical abstract: Abstract: Polymersomes represent a promising pharmaceutical vehicle for the delivery of hydrophilic therapeutic agents. However, modification of polymersomes with molecules that confer targeting functions remains challenging because of the strict requirements regarding the weight fractions of the hydrophilic and hydrophobic block polymers. In this study, based on the compatibility between cholesterol and polymeric carriers, polymersomes self-assembled by amphiphilic graft polyphosphazenes were endowed with a targeting function by incorporating the cholesterol-linked aptamer through a simple dialysis method. The aqueous interior of the polymersomes was employed to encapsulate water-soluble doxorubicin hydrochloride. In vivo experiments in tumor-bearing mice showed that the aptamer-anchored vesicle targeted accumulation at the tumor site, favorable penetration through tumor tissue, and incremental endocytosis into tumor cells. Correspondingly, the aptamer-anchored vesicle decreased systemic toxicity and effectively suppressed the growth of subcutaneous MCF-7 xenografts. These findings suggested that vesicles modified with targeted groups via hydrophobic supermolecular interactions could provide a platform for selective delivery of hydrophilic drug. Statement of Significance: Polymersomes have represented a promising type of pharmaceutical vehicles due to their predominant physical properties. However, it is still a challenge to endow polymersomes with active target function because of strict requirements of the weight fractions of hydrophilic polymer block to hydrophobic one. In this research, by taking advantage of the supermolecular interactions between amphiphilic graft polyphosphazene and cholesterol which was linked to aptamer AS1411, we prepared a targeted functional polymersome (PEP-DOX·HCl-Ap) through a simple method with high loading of water soluble anti-cancer drug doxorubicin hydrochloride. The in vivo experiments in MCF-7 tumor-bearing mice demonstrated several advantages of PEP-DOX·HCl-Ap vesicle such as prolonged circulation time in blood, targeted accumulation at tumor site, permeation through the tumor tissue and incremental endocytosis by tumor cells, which consequently resulted in the significantly improved anti-cancer efficacy. Moreover, this novel polymersome designed in this study has built a research platform to achieve targeted delivery of hydrophilic chemotherapeutics for cancer therapy.